THE RESPONSABILITY TO PROTECT AND THE USE OF FORCE IN INTERNATIONAL LAW - Piancastelli, Luís Paulo Bogliolo (Revista dos Estudantes de Direito da Universidade de Brasília, 2010)
The following article deals with the developments in recent years on the debate concerning humanitarian intervention and the framework of public international law regarding the use of force. Itspecifically focuses on how the doctrine of the Responsibility to Protect (R2P) has developed over theyears and why it cannot be seen as a contribution to the affirmation of a so-called “right” of humanitarian intervention.